Nilai Sosial Budaya dalam Novel Proelium Karya Febrialdi R - Deviyani Deviyani; Andrie Chaerul; Sutri Sutri (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This study aims to describe the socio-cultural values in the novel Proelium by Febrialdi R. The method used is qualitative research. The approach used in this research is the sociology of literature approach. data collection in this research is reading and taking notes. Then the results of this study can find the socio-cultural values contained in the novel Proelium by Febrialdi R.the socio-cultural values in question are polite, community condition, social interaction, and writing via social media. Socio-cultural values are the characters that Irham has when interacting in the community. Irham's habits in society create culture, one of which is courtesy. This research helps make readers aware that the socio-cultural values must be possessed by each individual to create positive habits of interacting in society.